Clinical, immunological, molecular and therapeutic findings in monogenic immune dysregulation diseases: Middle East and North Africa registry - BARIŞ, SAFA; ÖZEN, AHMET OĞUZHAN (My University, 2022)
© 2022Monogenic immune dysregulation diseases (MIDD) are caused by defective immunotolerance. This study was designed to increase knowledge on the prevalence and spectrum of MIDDs, genetic patterns, and outcomes in Middle East and North Africa (MENA). MIDD patients from 11 MENA countries (Iran, Turkey, Kuwait, Oman, Algeria, Egypt, United Arab Emirates, Tunisia, Jordan, Qatar, and Azerbaijan) were retrospectively evaluated. 343 MIDD patients (58% males and 42% female) at a median (IQR) age of 101 (42–192) months were enrolled. The most common defective genes were LRBA (23.9%), LYST (8.2%), and RAB27A (7.9%). The most prevalent initial and overall manifestations were infections (32.2% and 75.1%), autoimmunity (18.6% and 41%), and organomegaly (13.3% and 53.8%), respectively. Treatments included immunoglobulin replacement therapy (53%), hematopoietic stem cell transplantation (HSCT) (14.3%), immunosuppressives (36.7%), and surgery (3.5%). Twenty-nine (59.2%) patients survived HSCT. Along with infectious complications, autoimmunity and organomegaly may be the initial or predominant manifestations of MIDD.
Keywords: Tıp; Yaşam Bilimleri; Sağlık Bilimleri; Temel Bilimler; Medicine; Life Sciences; Health Sciences; Natural Sciences; Klinik Tıp (MED); Yaşam Bilimleri (LIFE); Klinik Tıp; İmmünoloji; ALERJİ; Clinical Medicine (MED); Life Sciences (LIFE); CLINICAL MEDICINE; IMMUNOLOGY; ALLERGY; İmmünoloji ve Alerji; Immunology and Allergy; Immunology; Autoimmune disorders; Genetic; Immune dysregulation; Inborn errors of immunity; Lymphoproliferation; Primary immunodeficiency